A Study On The Quality Of Material In Libyan Iron And Steel Industry - Ma Kridan, Frag Ahmed (2008)
The steel industry plays an important role in the production and supply of steel, which is a basic and important building material that is consume by the construction and the manufacturing industry. Like any other industry, the Libyan iron and steel industry requires the spare parts of the plant and machine, together with other consumable for the smooth operation of the production department. The aim of the research is to study the quality of materials as it relates to rejection of supplied spare parts and consumables in the Libyan iron and steel industry. The data for the research was obtained from the record of all the spare parts and consumables that were rejected in the general material department for the year 2004. The data was analyzed by descriptive statistics.